Ondansetron/Cyclodextrin inclusion complex nanofibrous webs for potential orally fast-disintegrating antiemetic drug delivery - Hsiung, Emmy; Celebioglu, Asli; Kilic, Mehmet Emin; Durgun, Engin; Uyar, Tamer (ELSEVIER, 2022)
Ondansetron (ODS) is an effective antiemetic drug which suffers from limited solubility and bioavailability during oral administration due to first-pass metabolism. However, these limitations can be mitigated through inclusion complexation with cyclodextrins (CDs). In this study, we have reported the electrospinning of polymer -free, free-standing ODS/CD nanofibrous webs (NW), a promising approach for developing a fast-disintegrating delivery system of an antiemetic drug molecule. Highly water soluble hydroxypropyl-beta-cyclodextrins (HP beta CD) were used as both complexation agent and electrospinning matrix. The computational study revealed that the 1/2 (drug/CD) stoichiometry was more favorable compared to 1/1. The ODS/HP beta CD NW was obtained with higher loading efficiency (-96 %) compared to the control sample of ODS/polyvinyl alcohol (PVA) NW (-80 %). The amorphous distribution of ODS raised by complexation and the highly water-soluble nature of HP beta CD resulted into faster and better release profile and quite faster disintegration property (-2 s) in artificial saliva than polymeric ODS/PVA NW. Here, ODS/HP beta CD NW was generated in the absence of a toxic solvent or chemical to enable the drug loading in an amorphous state. From all reasons above, ODS/HP beta CD NW might be a promising alternative to the polymeric based systems for the purpose of fast-disintegrating oral drug delivery.